PENGARUH PEMBERDAYAAN DAN KOMPETENSI TERHADAP PENINGKATAN KINERJA KARYAWAN CV. JAKAHARTA PALEMBANG - Nur Supriyadi; Fahmi Fadlillah Syaiful (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This study aims to examine the effect of employee competence and empowerment on improving employee performance at CV Jakaharta Palembang. Quantitative strategy was adopted as the research method in this study. Sixty employees were sampled in this investigation. Employees of CV Jakaharta Palembang were given questionnaires as part of the data collection methodology. Data analysis was conducted by multiple linear regression. SPSS 24 was used in the data processing of this study. The research findings show that employee performance is influenced by the empowerment component.